2013
DOI: 10.1038/am.2013.54
|View full text |Cite
|
Sign up to set email alerts
|

High-performance polypyrrole functionalized PtPd electrocatalysts based on PtPd/PPy/PtPd three-layered nanotube arrays for the electrooxidation of small organic molecules

Abstract: Here, we report novel high-performance polypyrrole (PPy) functionalized PtPd electrocatalysts based on PtPd/PPy/PtPd threelayered nanotube arrays (TNTAs) for the electrooxidation of small organic molecules, such as methanol, ethanol and formic acid, which are superior fuels for direct alcohol fuel cells (DAFCs) or direct formic acid fuel cells (DFAFCs). The unique hollow structures, array structures and sandwich-like structures of PtPd/PPy/PtPd TNTAs will provide fast transport and short diffusion paths for el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(41 citation statements)
references
References 67 publications
2
38
1
Order By: Relevance
“…Core–shell FePtM–PtFe (M=Pd, Au) nanowires with 2.5 nm FePtM seeds and 0.3–1.3 nm thick PtFe shells (Figure B) have been prepared by a seed‐mediated growth approach . PtPd/PPy/PtPd (PPy=polypyrrole) three‐layered nanotube arrays (Figure C) were fabricated by five‐step procedure . After the fabrication of ZnO nanorod arrays, PtPd layers were then electrodeposited onto the surface of ZnO nanorods to form PtPd/ZnO nanorod arrays.…”
Section: Controllable Synthesis Of Pt‐based Bimetallic Alloy Nanostrumentioning
confidence: 95%
“…Core–shell FePtM–PtFe (M=Pd, Au) nanowires with 2.5 nm FePtM seeds and 0.3–1.3 nm thick PtFe shells (Figure B) have been prepared by a seed‐mediated growth approach . PtPd/PPy/PtPd (PPy=polypyrrole) three‐layered nanotube arrays (Figure C) were fabricated by five‐step procedure . After the fabrication of ZnO nanorod arrays, PtPd layers were then electrodeposited onto the surface of ZnO nanorods to form PtPd/ZnO nanorod arrays.…”
Section: Controllable Synthesis Of Pt‐based Bimetallic Alloy Nanostrumentioning
confidence: 95%
“…after 10‐minute incubation of the Ag NWs with Ag(SCN) − , blue curve). Both types of nanotubes exhibit the characteristic methanol oxidation behaviour (Figure 4B) . The porous Au nanotubes displayed a surge in peak current at around −0.28 V (vs. Ag/AgCl) in the forward scan.…”
Section: Resultsmentioning
confidence: 98%
“…FAO on Pt usually follows a dual path mechanism (dehydrogenation path and dehydration path), in which the CO ads produced from the dehydration path would absorb and poison the Pt active sites by the strong Pt‐CO ads binding . Incorporation of other metals or oxides with Pd, such as Pt, Pb, Au, Ir, HoO x , or WO 2.72 , has been considered as an effective strategy to improve the activity and stability of Pd‐based catalysts. For instance, Du and co‐workers demonstrated that a well‐prepared ultrauniform and small PdBi nanodots had a high FAO activity compared to that of commercial Pd/C .…”
Section: Methodsmentioning
confidence: 99%